Differential Cadmium Distribution and Translocation in Roots and Shoots Related to Hyper-Tolerance between Tall Fescue and Kentucky Bluegrass - Dong, Qin; Xu, PeiXian; Wang, ZhaoLong (Frontiers in Plant Science, 2017)
Phytoremediation efficiency mainly depends upon the plant mechanism in uptake and translocation of the soil contaminants. Cadmium distributions and translocations in roots and shoots of tall fescue (Festuca arundinacea) and Kentucky bluegrass (Poa pratensis) were observed by fluorescence spectroscopy with a laser confocal scanning microscope. No difference in root Cd accumulations was detected between these two turfgrass species. Kentucky bluegrass transported more Cd into the stele for root-to-shoot translocation and resulted in significantly higher Cd concentrations in leaves. In tall fescue, the less Cd transported into the stele in roots and more Cd was excreted to the cuticle layer in leaves. These results suggested that both turfgrass species were hypertolerant to Cd through distinct distribution patterns in leaves and roots.